Adsorvente a base de glucomanano em dietas de frangos de corte alimentados com milho contaminado. - Lopes, Lorena Lacava (2011)
This study aimed to investigate the use of sterified glucomannan adsorbent on the productive performance of broilers of broilers fed mouldy corn.. A total of 1440 dayold broilers were allocated in pens, ten replications per treatment. Treatments were: T1 non-mouldy corn, without adsorbent (control); T2- non-mouldy corn with adsorbent; T3- mouldy corn without adsorbent and T4- mouldy corn with adsorbent. Weekly, birds and diets were evaluated for weight gain, feed intake, feed conversion, viability and efficiency factor. No significant interaction between corn and adsorbent was observed. Mouldy corn brought about a decrease in feed consumption, feed efficiency and viability. However, birds fed mycotoxin adsorbent showed better feed efficiency, viability and efficiency factor. These results indicate that the use of mouldy corn in broilers diets has negative effects on performance and the addition of absorbent improves feed conversion, efficiency factor and viability of the birds.